Convergence of temperate and tropical stream fish assemblages - (:unkn) unknown (My University, 2009)
Convergence des assemblages de poissons de cours d'eau tempérés et tropicaux. / The hypothesis of convergence takes the deterministic view that community (or assemblage) structure can be predicted from the environment, and that the environment is expected to drive evolution in a predictable direction. Here we present results of a comparative study of freshwater fish assemblages from headwater streams in four continents (Europe, North America, Africa and South America), with the general objective of testing whether these assemblages display convergent structures under comparable environmental conditions (i.e. assemblage position in the stream longitudinal continuum). We tested this hypothesis by comparing species richness and trophic guilds of those stream fish assemblages represented in available data from multiple sites on each continent. Independent of phylogenetic and historical constraints, fish assemblage richness and trophic structure in the four continents converged along the stream continua to a substantial degree. For the four continents, assemblage richness increased, the proportion of invertivorous species decreased, and the proportion of omnivorous species increased from upstream to downstream, supporting theoretical predictions of the river continuum concept. However, the herbivore/detritivore and piscivore guilds were virtually absent from our small European and North American stream sites, unlike our African and South American stream sites. This divergence can be linked to differences in energy availability between temperate and tropical systems.
Keywords: African Research